Atomic-scale visualization of oxide thin-film surfaces. Issue 1 (31st December 2018) - Iwaya, Katsuya; Ohsawa, Takeo; Shimizu, Ryota; Okada, Yoshinori; Hitosugi, Taro
Abstract: The interfaces of complex oxide heterostructures exhibit intriguing phenomena not observed in their constituent materials. The oxide thin-film growth of such heterostructures has been successfully controlled with unit-cell precision; however, atomic-scale understandings of oxide thin-film surfaces and interfaces have remained insufficient. We examined, with atomic precision, the surface and electronic structures of oxide thin films and their growth processes using low-temperature scanning tunneling microscopy. Our results reveal that oxide thin-film surface structures are complicated in contrast to the general perception and that atomically ordered surfaces can be achieved with careful attention to the surface preparation. Such atomically ordered oxide thin-film surfaces offer great opportunities not only for investigating the microscopic origins of interfacial phenomena but also for exploring new surface phenomena and for studying the electronic states of complex oxides that are inaccessible using bulk samples. Abstract :